Estimation of human absorbed dose of 99mTc-MAA using MIRD method based on animal data and comparison with MCNP simulation code: Estimation of absorbed dose of 99mTc-MAA using MIRD and MCNP method - Naserpour, Masoumeh; Mohammadi, Saeed; Shirmardi, Seyed Pezhman (Archives of Advances in Biosciences, 2021)
Introduction: 99mTc-Macro Aggregated-Albumin (99mTc-MAA) has been evaluated as a useful perfusion study agent. In this study, the human absorbed dose of 99mTc-MAA was estimated with MIRD and MCNP methods based on animal biodistribution data and finally compared with ICRP publication data. Materials and Methods: In this study, for investigating the biodistribution of 99mTc-MAA, after radiolabeling of MAA with Technetium-99m, it was injected to mice via the tail vein. After 1-120 min post injection, the mice were sacrificed and some of their tissues dissected and counted for calculating the percentage of the injected dose per gram (% ID/g) and the absorbed dose. Then, the obtained data was converted to equivalent data in human for each tissue. Results: Dose prediction shows that the highest absorbed dose is observed in the lungs (MIRD: 6.8E-2 mGy/MBq, MCNP: 6.32E-2 mGy/MBq). There is good agreement between the results obtained from MIRD and MCNP simulation for lungs. Conclusion: According to the present results and comparison with ICRP publication data, animal dissection model and simulation MCNP code can be useful tools for internally-absorbed dose estimation of pulmonary radiopharmaceuticals.